Fiscal Policy and the Exchange Rate-Current Account Nexus - Kim, Jun (IMF Working Papers; Working Paper ;, 2007)
By using a simple intertemporal model of the current account, I show that the exchange rate elasticity of the trade balance would ceteris paribus be smaller for countries with higher government spending ratios (relative to GDP) and with more limited scope for private consumption smoothing. This finding may have important implications for the design of adjustment programs and for resolving current global imbalances. It could also help explain and reconcile mixed empirical findings on trade elasticities.